The Frequency of Port-Site Infection in Laparoscopic Cholecystectomies (Medicine Today, 2021)
Introduction: Laparoscopic surgery was a revolution in the field of surgery. Despite many benefits, the technique is associated with certain complications including PSI. PSI, although less common is annoying both for the surgeon and the patient, and cripple the benefits of MSI. PSI not only increases the economic burden, pain and Hospital stay of patient but also harm the reputation of the attending Surgeon and hospital.Materials and Methods: This observational study carried out by the Department of general surgery at Medical College for Women & Hospital (MCWH), Uttara, Dhaka over a period of one year (July 2017 to June 2018). The study was carried out in 108 patients who underwent LC. AIM was to study the frequency of port site infection.Results: In the current study, 108 patients including 92 females and 16 males were operated. A total of 12 patients had PSI. Infection was seen in one male patients and 11 female patients. Age range was 20-75 years. Port –site involved was epigastric, which developed infection in 7 patients, followed by umbilical port which got infected in 5 patients. Gall bladder was extracted through epigastric port site in 29 patients and through umbilical port site in 79 patients. 7 cases are superficial infection with foreign body reaction, 2 cases are deep infection and 3 cases are mycobacterial tuberculous infection.Conclusion: LC is associated with a low risk of port site infection which in most cases is only superficial and responds to local measures. Infection is most commonly seen at port site through which gall bladder was extracted.Medicine Today 2021 Vol.33(1): 22-26